GERMPLASM PRESERVATION BY CRYOPRESERVATION: USE OF NEW BIOTECHNOLOGY TO MAINTAIN GENETIC DIVERSITY IN LABIATAE SPECIES - Senula, A.; Keller, E. R Joachim (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Many Labiatae species are of potential interest as medicinal and aromatic plants. Therefore, micropropagation was established, which includes clonal maintenance. Furthermore, some species are endangered. in vitro culture and cryopreservation increasingly contribute to the germplasm maintenance in genebanks, especially of vegetatively propagated germplasm, like in mint (Mentha spp.). Various cryopreservation methods are used worldwide. The germplasm collection of the German Central Crop Collection maintains 148 accessions of various mint species in vitro using slow growth conditions at 2°C and 10°C. Cryopreservation is applied using droplet vitrification with the cryoprotectant PVS2. At present, the cryopreserved mint collection consists of 24 accessions. The average regeneration rate is 62%. Regeneration is depending on the genotype. Recently was found that endophytes play a major role in cryopreservation success. Antibiotics are applied to support survival and regeneration in critical phases after rewarming. Despite good success of cryopreservation in various mint species, this method is still not fully applicable to another Labiatae genus, Orthosiphon. Here, regeneration rate is 82% in controls contrasting to 4% in cryopreserved samples. In vitro maintenance of these plants is possible but labour-intensive because they are not storable at low temperatures. Various measurements of the target organs were performed to elucidate the background of these differences. Differential scanning calorimetry informs about the thermal transitions of tissue water critical for storability. Its results revealed that the pretreatment time must be longer comparing to that needed for mint.